SPECIFICITY OF KNOWLEDGE IN THE CONTEXT OF SOCIO-CULTURAL DEVELOPMENT - Skyba, Ivan (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2022)
Introduction. The timeliness of the study is determined by the global nature of the problems in the development of modern society. The current global problems are the result of a certain development strategy, and, above all, a certain type of worldview that has developed in a particular historical period. Therefore, the solution of existing problems is associated with finding the optimal worldview, which, in turn, determines the specifics of the knowledge base of socio-cultural activities (the specifics of worldview and instrumental knowledge). The aim and tasks are a study of the specifics of knowledge in the context of socio-cultural development. Research methods: The methodological strategy of the research is based on socio-cultural, cultural-historical, systemic and comparative methodological approaches in their dialectical unity. Research results. In each historical epoch, a certain type of worldview is formed, which determines the specifics of human activity. There is a certain relationship between worldview knowledge, which is the basis of a certain type of worldview-orientation, and instrumental knowledge, which is designed in accordance with this type of worldview. Such interdependence of worldview and instrumental knowledge has a decisive influence on the specifics of socio-cultural development in general and the relevant era in particular. Discussion examines the specifics of knowledge used in the field of social relations in Antiquity. Conclusion. The knowledge basis of socio-cultural activity is worldview and instrumental knowledge, the specificity of which is determined by a certain type of worldview that has developed in different historical periods.